Clinical significance of in vivo cytarabine-induced gene expression signature in AML. Issue 4 (2nd April 2016) - Lamba, Jatinder K.; Pounds, Stanley; Cao, Xueyuan; Crews, Kristine R.; Cogle, Christopher R.; Bhise, Neha; Raimondi, Susana C.; Downing, James R.; Baker, Sharyn D.; Ribeiro, Raul C.; Rubnitz, Jeffrey E.
Abstract: Despite initial remission, ∼60–70% of adult and 30% of pediatric patients experience relapse or refractory AML. Studies so far have identified base line gene expression profiles of pathogenic and prognostic significance in AML; however, the extent of change in gene expression post-initiation of treatment has not been investigated. Exposure of leukemic cells to chemotherapeutic agents such as cytarabine, a mainstay of AML chemotherapy, can trigger adaptive response by influencing leukemic cell transcriptome and, hence, development of resistance or refractory disease. It is, however, challenging to perform such a study due to lack of availability of specimens post-drug treatment. The primary objective of this study was to identify in vivo cytarabine-induced changes in leukemia cell transcriptome and to evaluate their impact on clinical outcome. The results highlight genes relevant to cytarabine resistance and support the concept of targeting cytarabine-induced genes as a means of improving response.